Deploying Low Carbon Public Procurement to Accelerate Carbon Removal - Dunford, Eric; Niven, Robert; Neidl, Christopher (Frontiers in Climate, 2021)
Carbon dioxide removal (CDR) will be required to keep global temperature rise below 1.5° Celsius based on IPCC models Greater adoption of carbon capture utilization and storage (CCUS) technologies will drive demand for CDR Public procurement of low carbon materials is a powerful and under-utilized tool for accelerating the development and of CCUS through a targeted and well-regulated approach The policy environment is nascent and presents significant barriers for scaling and guiding emerging technology solutions The concrete sector has unique attributes that make it ideally suited for large-scale low-carbon public procurement strategies This sector offers immediate opportunities to study the efficacy of a supportive policy and regulatory environment in driving the growth of CCUS solutions